Finite Volume Non-hydrostatic Pressure Model for the Simulation of Landslides - Echeverribar, Isabel; García Navarro, Pilar; Brufau, Pilar (Jornada de Jóvenes Investigadores del I3A, 2022)
A Finite Volume (FV) numerical scheme previously designed for the hydrostatic Shallow Water Equations (SWE) is extended to compute non-hydrostatic pressure (NHP) in order to simulate dispersive waves. These waves are usually generated by landslides and are of importance in coastal alarm systems. The model is validated in 1D comparing with laboratory measurements and the results highlight the importance of  including the NHP terms in the model to achieve a good agreement between numerical and experimental results.